Chloride intracellular channel 1 participates in migration and invasion of hepatocellular carcinoma by targeting maspin. Issue 1 (January 2015) - Wei, Xuyong; Li, Jie; Xie, Haiyang; Wang, Hangxiang; Wang, Jianguo; Zhang, Xuanyu; Zhuang, Runzhou; Lu, Di; Ling, Qi; Zhou, Lin; Xu, Xiao; Zheng, Shusen
Abstract Background and Aim Our previous proteomic research found that chloride intracellular channel 1 (CLIC1) was upregulated in hepatocellular carcinoma (HCC) tissues with portal vein tumor thrombus. The present study aimed to determine the role of CLIC1 in HCC invasion. Methods Immunohistochemistry was used to explore protein expression of CLIC1 in 15 cirrhotic tissues and 69 pairs of HCC and paracarcinoma tissues. Small interfering RNA (siRNA) and plasmids were transfected into HepG2 and SMMC7721 cells, and the in vitro function of CLIC1 in these cells were assessed with cell counting kit‐8 assays, cell apoptosis assays, scratch assays, and transwell assays. Microarray analysis was also performed to further explore the candidate genes related to CLIC1. Results Our results confirmed that upregulated CLIC1 expression was significantly correlated with vascular invasion (P = 0.034) in HCC tissues. Knockdown of CLIC1 decreased cell viability and the invasive potency of HepG2 cells, whereas CLIC1 overexpression resulted in an opposite effect in SMMC7721 cells. Microarray analysis identified 618 genes that were differentially expressed (fold change ≥ 2, P < 0.05) between HepG2 cells transfected with CLIC1 siRNA and the negative control. Further studies indicate that knockdown of CLIC1 increased maspin expression and reduced vascular endothelial growth factor (VEGF), matrixmetalloproteinase‐2 (MMP2), MMP9, MMP11, and MMP12 expression. In contrast, overexpression of CLIC1 decreased maspin expression and increased VEGF, MMP2, MMP12, and MMP13 expression. Conclusions CLIC1 protein expression is significantly correlated with vascular invasion, and the present study suggests a previously unknown mechanism of CLIC1‐mediated control of HCC invasiveness by targeting maspin.